Critical challenges and emerging opportunities in hepatitis C virus research in an era of potent antiviral therapy: Considerations for scientists and funding agencies - Bartenschlager, Ralf; Lohmann, Volker (Virus research, 2018)
The development and clinical implementation of direct-acting antivirals (DAAs) has revolutionized the treatment of chronic hepatitis C. Infection with any hepatitis C virus (HCV) genotype can now be eliminated in more than 95% of patients with short courses of all-oral, well-tolerated drugs, even in those with advanced liver disease and liver transplant recipients. DAAs have proven so successful that some now consider HCV amenable to eradication, and continued research on the virus of little remaining medical relevance. However, given 400,000 HCV-related deaths annually important challenges remain, including identifying those who are infected, providing access to treatment and reducing its costs. Moreover, HCV infection rarely induces sterilizing immunity, and those who have been cured with DAAs remain at risk for reinfection. Thus, it is very unlikely that global eradication and elimination of the cancer risk associated with HCV infection can be achieved without a vaccine, yet research in that direction receives little attention. Further, over the past two decades HCV research has spearheaded numerous fundamental discoveries in the fields of molecular and cell biology, immunology and microbiology. It will continue to do so, given the unique opportunities afforded by the reagents and knowledge base that have been generated in the development and clinical application of DAAs. Considering these critical challenges and new opportunities, we conclude that funding for HCV research must be sustained.